Angiotensin II type 1 receptor A1166C gene polymorphism and essential hypertension in the Efiks of Calabar (2009)
Hypertension is a multifactoral disorder because of the interaction of risk genes and environmental factors. The angiotensin II is a well known vasoconstrictor that exerts most of its influence through the angiotensin Il type 1 receptor The A 1166C polymorphism is a single base substitution of adenine for cytosine at position 1166 in the 3' untranslated region of the gene. There are conflicting reports on the association of the Al166C polymorphism with cardiovascular diseases such as prevalent hypertension, left ventricular hypertrophy, and pregnancy induced hypertension. These variations were attributed to ethnic differences in different populations. We investigated the association of the All66C polymorphism with hypertension in 100 individuals from the Efik tribe who were matched for gender and sample size. PCR-RFLP analysis was carried out to determine the allele frequency of the gene. The genotype frequencies were 48, 2 and 47, 3 for the AA, AC genotypes respectively in the patient and control groups. No individual with the CC genotype was observed in the study population. The frequency or the C allele was 0.03 and 0.02 in the control and the patient population. The genotype and allele frequency did not conform to the Hardy-Weinberg theory. Using regression analysis, age and diastolic were positive predictors for SBP, r=0.0.50; systolic was the only predictor for DBP in the patient group. Diastolic was the only predictor for SBP, r= 0.656 while age and systolic were positive predictors for DBP r= 0.718 in the control group. Gender, BMI, Al166C polymorphism and other independent varilables were not predictors for SBP and DBP in the population. P= 0.05, odds ratio 0.65, 95% CI (0.13 to 3.44). The Al166C polymorphism is not an independent risk factor for essential hypertension in the study population.